Features of staff management of organizations providing social services - Бутиліна, О. В. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2019)
The article is about analysis of features of organization providing social services. It is noted that the staff management system in these organizations should be developed taking into account the external and internal environment, the specifics of the work and professional risks of specialists. It is supposed directions of work with staff that are based on the personal needs of employees and the purposes of the organization. It is noted that these directions should include work on staff training, system of load distribution and comprehensive motivation.